Pengaruh Kualitas Cahaya dan Frekuensi Aplikasi Paclobutrazol Terhadap Pertumbuhan dan Hasil Tanaman Krisan (Chrysanthemum morifolium) - Ryan Firman Syah ryan (Universitas Merdeka Madiun, 2023)
Abstract-This research aims to determine the effect of light quality and frequency of application of Paclobutrazol on the growth and yield of chrysanthemum plants. The research was carried out from February to April 2023 using factorial experiments and arranged in a Split Plot Design consisting of a Main Plot and a Sub Plot. The main plot is the influence of light quality using three different colours of light: white, red, and blue. The subplot is the frequency of application of Paclobutrazol, which consists of 4 types, namely 0 times, 1 time, 2 times and 3 times. The data analysis used in this research is the analysis of variance with a confidence level of 5%. The results showed an interaction between light quality and the frequency of Paclobutrazol application on the parameters of stem diameter and leaf area. The quality of light has a good influence on the parameters of plant height, flower colour, flower quality, number of flowers, number of leaves and flower diameter. The frequency of application of Paclobutrazol has a good influence on the parameters of plant height, flower colour, flower quality, number of flowers, number of leaves and flower diameter. The best plant height is 106.39 cm, the most significant number of leaves is 15.5, the best leaf area is 89.42 cm2, the best stem diameter is 0.41 inches, the best flower colour with a score of 2.5, the best flower quality with a score of 2.8, the largest flower diameter is 7.93 cm. The most significant number of flowers is 5 flowers.